The Hidden Epidemic: The Prevalence and Impact of Concurrent Liver Diseases in Patients Undergoing Liver Transplantation in Australia and New Zealand. Issue 8 (15th July 2022) - Howell, Jess; Majumdar, Avik; Fink, Michael; Byrne, Mandy; McCaughan, Geoff; Strasser, Simone I.; Crawford, Michael; Hodgkinson, Peter; Stuart, Katherine A.; Tallis, Caroline; Chen, John; Wigg, Alan; et al.
Abstract : Background: Prevalence of concurrent liver diseases among liver transplant recipients and impact on posttransplant outcomes are unknown. Methods: This retrospective study included adult liver transplants between January 1‚ 1985‚ and December 31‚ 2019‚ from the Australian and New Zealand Liver and Intestinal Transplant Registry. Up to 4 liver disease causes were recorded for each transplant; concurrent liver diseases were defined as >1 liver disease indication for transplantation, excluding hepatocellular carcinoma. Impact on posttransplant survival was determined using Cox regression. Results: A total of 840 (15%) of 5101 adult liver transplant recipients had concurrent liver diseases. Recipients with concurrent liver diseases were more likely male (78% versus 64%) and older (mean age 52 versus 50 y). A higher proportion of liver transplants for hepatitis B (12% versus 6%), hepatitis C (33% versus 20%), alcohol liver disease (23% versus 13%), and metabolic-associated fatty liver disease (11% versus 8%, all P < 0.001) were identified when all indications were included than with primary diagnosis only. The number and proportion of liver transplants performed for concurrent liver diseases have increased from 8 (6%) during Era 1 (1985–1989) to 302 (20%) during Era 7 (2015–2019; P < 0.001). Concurrent liver diseases were not associated with increased posttransplant mortality (adjusted hazard ratio, 0.98, 95% confidence interval, 0.84-1.14). Conclusions: Concurrent liver diseases are increasing among adult liver transplant recipients in Australia and New Zealand; however, they do not appear to impact posttransplant survival. Reporting all liver disease causes in the transplant registry reports provides more accurate estimates of liver disease burden. Abstract :